Study of the Immunobiological Properties of Surface Protein-Containing Antigens of Streptococcus pneumoniae Serotype 6B - O. M. Kukina; I. M. Gruber; N. K. Akhmatova; O. V. Zhigunova; E. A. Kurbatova; N. B. Egorova; N. E. Yastrebova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Prevention of pneumococcal infection in the Russian Federation is carried out by imported polysaccharide and conjugated vaccines without taking into account the circulation of clinically significant isolates, which leads to the growth of previously rare genetic lines and serotypes that are not part of the vaccines, and does not protect against the carriage. Serotype-independent vaccines are being developed based on protective proteins and variants of whole-cell vaccines capable of providing a cross-protective effect against pneumococcus. Objective. Investigation of the protective properties of surface protein-containing antigens isolated from the immunogenic strain S. pneumoniae 6B No. 296 and their influence on key effectors of innate immunity. Materials and methods. S. pneumoniae 6B No. 296 was cultured in a semi-synthetic medium under stationary conditions at 5% CO2 for 5-7 hours. From inactivated bacterial cells, the experimental initial protein-containing preparation was obtained - an aqueous extract (A/E), from which a 30-100 kDa fraction (FR) isolated, and from the sterile culture supernatant, the protein-containing preparation - supernatant (S/N); in the preparations, the protein content was determined. Immunobiological properties were studied after double intraperitoneal immunization of BALB/c mice. The protective activity was determined after infection with virulent strains of S. pneumoniae serotypes 6B No. 1121 and No. 3. Phagocytic activity was studied by the number of granulocytes that absorbed heat-killed FITC-labeled S. aureus cells. The expression of Toll-like receptors (TLRs) and the subpopulation structure of mouse spleen lymphocytes were investigated after staining with FITC/PE-labeled monoclonal antibodies using flow cytometry. Statistical analysis of materials was carried out using parametric and non-parametric methods using the software package «Statistica for Windows», ver. 7.0 (Stat Soft, Inc). Results. The protective effect of FR upon infection with virulent strains of homologous (6B No. 1121) and heterologous serotypes (3 No. 3) was established; S/N protected mice when infected with strain 3 No. 3. All the studied drugs led to an increase in the number of phagocytic cells (the greatest effect was observed upon immunization with FR and S/N) and stimulated the expression of TLR2 and TLR4 positive cells (there was an increase in the number of TLR2-expressing cells during immunization with FR compared with A/E). When studying the immunophenotype of mouse lymphocytes, it was noted that the preparations induced the expression of effectors of innate and adaptive immunity. Conclusions. As a result of the studies, it was shown that the protective surface protein-containing fraction with MM 30-100 kDa is from tested experimental preparations the most active stimulator of innate and adaptive immunity, and requires further study to determine the possibility of using the serotype-independent pneumococcal vaccine in the development.